Study on withdrawal load resistance of screw in wood-based materials: experimental and numerical. Issue 1 (2nd January 2023) - Hu, Wengang; Liu, Yan; Konukcu, Arif Caglar
ABSTRACT: The effects of screw diameter, pilot hole, and material type on withdrawal load resistance (WLR) of screw driven in medium density fibreboard (MDF) and particleboard (PB) were investigated through using experimental and numerical methods. Meanwhile, the results of experimental tests and numerical analysis were compared with the empirical equations. The results showed that (1) the material type and the diameter of screw had significant effects on the WLR, but the pilot hole was not; (2) the equations proposed in Eurocode 5 had better performance in predicting WLRs of screw in both MDF and PB than the other equations; (3) density distributions of wood-based materials affected the mechanical behaviours of WLR of screw; (4) finite element model (FE-model) established could be used to simulate the WLR of screw in wood-based samples; (5) the complex FE-model considering threads of screw can reflect the stress distributions on threads in detail, which contributes to optimal design of threads geometry of screws. And the simplified FE-model without considering threads of screw had advantages in predicting the WLR with higher accuracy.